Critical illness polyneuromyopathy (literature review) - G. P. Plotnikov; M. R. Chuiko; A. N. Kudryavtsev; I. B. Hadzhiev; E. A. Kovrazhkina (Вестник анестезиологии и реаниматологии)
Neuromuscular disorders are extremely common in critically ill patients; they significantly affect the recovery time and limit the quality of subsequent  life. Until now, it is difficult to assess the presence of such disorders in intensive care units. The presented literature analysis of the current state of  the issues of epidemiology, pathogenesis and pathophysiology of critical illness polyneuromyopathy (CIPNM) determines the current directions  in the diagnosis and treatment of this pathology